2014
DOI: 10.15447/sfews.2014v12iss3art1
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Prey Selection, and Body Condition of Age-0 Delta Smelt, Hypomesus transpacificus, in the Upper San Francisco Estuary

Abstract: The Delta Smelt, an endangered fish, has suffered a long-term decline in abundance, believed to result from, in part, to changes in the pelagic food web of the upper San Francisco Estuary. To investigate the current role of food as a factor in Delta Smelt wellbeing, we developed reference criteria for gut fullness and body condition based on allometric growth. We then examined monthly diet, prey selectivity, and gut fullness of larvae and juvenile Delta Smelt collected April through September in 2005 and 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 47 publications
6
94
0
Order By: Relevance
“…This could be because of a strong surface orientation in visually feeding sub-adult Delta Smelt (Slater and Baxter 2014). Feyrer et al (2013) observed Delta Smelt throughout the water column on flood tides and only in the lower portion of the water column on ebb tides.…”
Section: Investigation Of Tow Methodsmentioning
confidence: 99%
“…This could be because of a strong surface orientation in visually feeding sub-adult Delta Smelt (Slater and Baxter 2014). Feyrer et al (2013) observed Delta Smelt throughout the water column on flood tides and only in the lower portion of the water column on ebb tides.…”
Section: Investigation Of Tow Methodsmentioning
confidence: 99%
“…However, the decline in delta smelt is due at least in part to food limitation at various life stages (Bennett, 2005;Slater & Baxter, 2014;Hammock et al, 2015). Primary productivity and abundance of the copepod prey of this fish have been low since * 1987 mainly because of grazing by the clam Potamocorbula amurensis, introduced in 1986 (Cloern & Jassby, 2012).…”
Section: Study Site and Speciesmentioning
confidence: 99%
“…After its introduction, P. forbesi was most abundant in waters ranging in salinity from 0 to 16 (Orsi & Walter, 1991), although it is now limited to salinity below * 5 (Kayfetz & Kimmerer, 2017). P. forbesi is an important food source for larvae and juveniles of pelagic fishes (Meng & Orsi, 1991;Moyle & Leidy, 1992;Bryant & Arnold, 2007) and makes up over half of the summer-autumn diet of delta smelt (Nobriga, 2002;Slater & Baxter, 2014). P. forbesi is a suspension-feeder, consuming phytoplankton, and microzooplankton (Bouley & Kimmerer, 2006;York et al, 2014;Bowen et al, 2015).…”
Section: Study Site and Speciesmentioning
confidence: 99%
“…As most fish grow, they progress to larger foods, such as mysids, amphipods and other epibenthic invertebrates. Filter feeders such as American (Alosa sapidissima) and threadfin (Dorosoma petenense) shad, and planktivores such as delta and longfin (Spirinchus thaleichthys), smelt remain largely tied to the pelagic food web, although they use epibenthic organisms such as mysids at least periodically (Moyle et al 1992;Feyrer et al 2003;Feyrer et al 2007;Slater and Baxter 2014).…”
Section: Diagram 5-secondary Production To Predatorsmentioning
confidence: 99%
“…There are few opportunities for grounded carbon to return to the pelagic web, except through microbial production that supplies the cyclopoid copepod L. tetraspina (Linkage 4.25) and some calanoid copepods (Linkage 4.22) with supplemental support. Although L. tetraspina is the numerical and biomass dominant copepod in the LSZ, it is not an important prey item for fishes (Slater and Baxter 2014), which may account for its high abundance (Bouley and Kimmerer 2006). Thus, L. tetraspina is probably grounded back into the detrital web, or advected out of the system.…”
Section: Sidebarmentioning
confidence: 99%